2016
DOI: 10.1002/chir.22668
|View full text |Cite
|
Sign up to set email alerts
|

Differential in radiosensitizing potency of enantiomers of the fatty acid synthase inhibitor C75

Abstract: The elevated activity of fatty acid synthase has been reported in a number of cancer types. Inhibition of this enzyme has been demonstrated to induce cancer cell death and reduce tumor growth. In addition, the fatty acid synthase inhibitor drug C75 has been reported to synergistically enhance the cancer‐killing ability of ionizing radiation. However, clinical use of C75 has been limited due to its producing weight loss, believed to be caused by alterations in the activity of carnitine palmitoyltransferase‐1. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We have previously showed that the fatty acid synthase inhibitor C75 sensitized prostate cancer cells to ionizing radiation [20]. Although the potential use of C75 has been limited due to side effects of appetite suppression and weight loss [51], this may be overcome using enantiomers of C75 which retain anti-tumor and radiosensitizing activity in the absence of anorexia [35, 52]. We demonstrate here that C75 is able to enhance the clonogenic killing activity of AICAR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have previously showed that the fatty acid synthase inhibitor C75 sensitized prostate cancer cells to ionizing radiation [20]. Although the potential use of C75 has been limited due to side effects of appetite suppression and weight loss [51], this may be overcome using enantiomers of C75 which retain anti-tumor and radiosensitizing activity in the absence of anorexia [35, 52]. We demonstrate here that C75 is able to enhance the clonogenic killing activity of AICAR.…”
Section: Discussionmentioning
confidence: 83%
“…For the determination of optimal sequencing of therapeutic agents, three different combination treatment schedules were assessed: (i) radiation and AICAR administered simultaneously, (ii) radiation administered 24 h before AICAR, (iii) radiation administered 24 h after AICAR. After treatment, cells were seeded for clonogenic survival assay as previously described [20, 35]. Cells were incubated at 37° C in 5% CO 2 for 13 days.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the (-)-C75 enantiomer was responsible for the anti-tumor properties, whereas (þ)-C75 induced the anorectic effects associated with the commonly used racemic mixture, (AE)-C75. 26 Cytotoxicity of the (-)-C75 enantiomer was also similar to (AE)-C75 in PC3 and LNCaP, and importantly, the radiosensitizing properties of (-)-C75 were similar to those of (AE)-C75, 27 indicating that it may be possible to retain the anti-tumor and radiosensitizing effects of this drug while preventing the unwanted weight loss. This highlights the importance of understanding the mechanisms by which C75 induces radiosensitization and whether other FASN inhibitors have similar effects when directly compared in the same models.…”
Section: Introductionmentioning
confidence: 84%